2021
DOI: 10.1088/1748-9326/abd0ab
|View full text |Cite
|
Sign up to set email alerts
|

Climate impacts associated with reduced diet diversity in children across nineteen countries

Abstract: It is widely anticipated that climate change will negatively affect both food security and diet diversity. Diet diversity is especially critical for children as it correlates with macro and micronutrient intake important for child development. Despite these anticipated links, little empirical evidence has demonstrated a relationship between diet diversity and climate change, especially across large datasets spanning multiple global regions and with more recent climate data. Here we use survey data from 19 coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 51 publications
1
12
0
Order By: Relevance
“…None applied a climate or rainfall variability pattern as proposed here. Additionally, we only found a single publication that explicitly addressed the link between climate variability and diets, but excluded child undernutrition ( 77 ). Here, the authors associated rainfall variability in the previous year to child dietary diversity in a multi-country analysis.…”
Section: Discussionmentioning
confidence: 99%
“…None applied a climate or rainfall variability pattern as proposed here. Additionally, we only found a single publication that explicitly addressed the link between climate variability and diets, but excluded child undernutrition ( 77 ). Here, the authors associated rainfall variability in the previous year to child dietary diversity in a multi-country analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research found that a warm temperature anomaly in the previous year was associated with lower dietary diversity in the current year among children in several regions. 46 This finding suggests that seasonal forecasts could potentially be used to guide nutrition interventions. However, further research is needed to characterize the timing and nature of the temperature anomalies and to identify pathways through which dietary diversity is affected.…”
Section: A Roadmapmentioning
confidence: 99%
“…3 Because of the negative effects of climate change on food security, undernutrition, including micronutrient deficiency, is identified as one of the biggest threats to child health, especially for children in resource poor settings. 4 However, most of the focus on child health has been on the first five years of life, evidenced in the significant investment and progress in the health and nutrition of infants and young children over the past five decades. 5 Given the potential impact of climate change on child health and nutrition, and to safeguard the investment in infants and pre-school children, existing efforts must continue, but increased attention must be given to protecting and promoting school aged children's nutrition so they can develop and grow into healthy adults.…”
mentioning
confidence: 99%
“…It is estimated that currently one billion children live in countries at extreme risk from the effects of climate change 3. Because of the negative effects of climate change on food security, undernutrition, including micronutrient deficiency, is identified as one of the biggest threats to child health, especially for children in resource poor settings 4. However, most of the focus on child health has been on the first five years of life, evidenced in the significant investment and progress in the health and nutrition of infants and young children over the past five decades 5.…”
mentioning
confidence: 99%